Growth peculiarities and magnetic properties of (LuBi)3Fe5O12 films by LPE method - Syvorotka, I. I.; Syvorotka, I. M.; Ubizskii, S. B. (Видавництво Львівської політехніки, 2012)
The series of (LuBi)3Fe5O12 film were grown on (111) oriented GGG substrate with diameters 1, 2 and 3 inch by liquid phase epitaxy using Bi2O3-base flux. Different types of surface morphology on the grown films were observed. The films’ surface was smooth and mirror while the film thickness was less than 13 μm and becomes rough for thickness above this value. The grown films were characterized by measuring magnetization loops and magneto-optic Faraday rotation under magnetization reversal as well as ferromagnetic resonance (FMR). All films with mirror surface demonstrate the in-plane magnetization, high Faraday rotation and FMR linewidth about 0.8 Oe at 9.1 GHz and room temperature.
Keywords: iron garnet; liquid phase epitaxy; surface morphology; magnetic properties